Predicting managerial styles: Is the Myers-Briggs Type Indicator still useful? - Erita Yuliasesti Diah Sari; Khoiruddin Bashori (Journal of Education and Learning (EduLearn), 2020)
The managerial ability for leaders becomes a critical matter to achieve organizational effectiveness. This study aims to describe the profile of school principals in Yogyakarta. A total of 39 principals in elementary school and senior high school participated in this study. Data was collected using the Myers-Briggs Type Indicator (MBTI) and Management Style Diagnostic Test (MSDT). The results showed that the dominant personality character is the components of openness, relationships, confidence, persistence, and combined with opportunities for creative and macro thinking. The principal's management style is dominated by Bureaucrat's type, which signifies compliance with the organization's rules and regulations and, combined with the Developer that allows a harmonious relationship between subordinate superiors to make efforts to develop.